2019
DOI: 10.1186/s12967-019-2055-4
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma rendered susceptible to NK-cell attack by TGFβ neutralization

Abstract: Background Medulloblastoma (MB), the most common pediatric brain cancer, presents with a poor prognosis in a subset of patients with high risk disease, or at recurrence, where current therapies are ineffective. Cord blood (CB) natural killer (NK) cells may be promising off-the-shelf effector cells for immunotherapy due to their recognition of malignant cells without the need for a known target, ready availability from multiple banks, and their potential to expand exponentially. However, they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Although the overall expression of cytokines is very low, exogenous administration of cytokines or inhibitors may be a useful target for immunotherapy. For example, TGF-β neutralization facilitated NK-cell induces MB suppression ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall expression of cytokines is very low, exogenous administration of cytokines or inhibitors may be a useful target for immunotherapy. For example, TGF-β neutralization facilitated NK-cell induces MB suppression ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…GBM cells do express several activator ligand for NK receptors, as for example MHC class I polypeptide-related sequence A (MICA) (29) ligand for NKG2D + present on NK cells, as well as CD155 and CD112 recognized by TIGIT and CD96 receptors (30). Indeed, it has been proved that NK cells exert lytic activity toward Medulloblastoma (MB) and GBM cell lines, both in in vitro (31)(32)(33) and in vivo models (31,34,35). Nevertheless, NK cell activity needs to be optimized in order to overcome inhibition exerted by tumor intrinsic and TME-associated factors.…”
Section: Non-engineered Immune Cell Approachesmentioning
confidence: 99%
“…Even if NK cells penetrate the tumor, they encounter an array of immune suppressive factors, such as tumor secreted transforming growth factor-beta (TGF-β), that may downregulate NK activity regardless of genetic modifications [147][148][149]. It has been suggested that a dominant negative TGF-β receptor that inhibits TGF-β signaling or a chimeric receptor that converts TGF-β to an activation signal may provide potential strategies to overcome NK cell exhaustion [150,151].…”
Section: Limitations Of Nk Cell Therapiesmentioning
confidence: 99%